2015
DOI: 10.1039/c5ra18697h
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid materials of pyrene substituted phthalocyanines with single-walled carbon nanotubes: structure and sensing properties

Abstract: Hybrid materials of single walled carbon nanotubes (SWCNT) were obtained by their non-covalent functionalization with asymmetrically polyoxyethylene substituted metal-free, copper(ii) and cobalt(ii) phthalocyanines bearing one pyrene group as a substituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 62 publications
(83 reference statements)
3
34
0
Order By: Relevance
“…The amount of ZnPc molecules covalently bonded to SWCNT is 1.8 times higher than that of ZnPc molecules non-covalently bonded to SWCNT. The correlation between the amount of adsorbed pyrene-substituted phthalocyanine molecules (MPcpy, M=Cu, Co, 2H) in SWCNT-based hybrids and their sensor responses have already been described in the literature [41]. Both SWCNT-based hybrids exhibit higher response toward NH 3…”
Section: Sensor Properties Studymentioning
confidence: 81%
See 2 more Smart Citations
“…The amount of ZnPc molecules covalently bonded to SWCNT is 1.8 times higher than that of ZnPc molecules non-covalently bonded to SWCNT. The correlation between the amount of adsorbed pyrene-substituted phthalocyanine molecules (MPcpy, M=Cu, Co, 2H) in SWCNT-based hybrids and their sensor responses have already been described in the literature [41]. Both SWCNT-based hybrids exhibit higher response toward NH 3…”
Section: Sensor Properties Studymentioning
confidence: 81%
“…It was shown that the interaction of asymmetric zinc(II) phthalocyanine containing 5 one pyrene substituent with SWCNTs is more favorable than in the case of symmetric without pyrene counterpart that provided a higher sensor response toward ammonia vapor. The influence of central metal in the phthalocyanine molecule on sensor response was also verified [41,42].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These macrocycles have been appended to CNTs to overcome their inherently low conductivity and surface‐to‐volume ratio; thus allowing them to be used in a chemiresistor approach for sensing. In particular, coordinated phthalocyanines attached to CNTs have been applied toward sensing reducing gases, such as NH 3 and H 2 S . Liang et al.…”
Section: Cnt‐based Gas Sensorsmentioning
confidence: 99%
“…These macrocycles have been appended to CNTst oo vercome their inherently low conductivity and surface-to-volume ratio;t hus allowing them to be used in a chemiresistor approach for sensing. In particular,c oordinated phthalocyanines attachedt oC NTsh ave been appliedt oward sensing reducingg ases, such as NH 3 [91,94] and H 2 S. [95] Liang et al prepared different metal(II) phthalocyanine (MPc)/ MWCNT hybridst hrough p-p stacking, and studied the effect of the metal center on the sensitivity of MPc/MWCNTst oward NH 3 . [91] The sensitivity of MPc/MWCNTst owardN H 3 decreased in the order of Co > Zn > Cu > Pb > Pd % Ni (Figure 10).…”
Section: Organometallic Compound/cntg As Sensorsmentioning
confidence: 99%